Productive thinking and its relationship with the beliefs of students of Department Mathematics of at the Faculty of Basic Education (Journal of the College of Basic Education, 2022)
The research aimed to identify research is to the relationship between productive thinking and cognitive beliefs among students of the College of Basic Education, and the research sample consisted of (187) male and female students from the Department of Mathematics at the College of Basic Education for the academic year (2018/2019). To achieve the goals of the research, the researcher prepared a measure that measures cognitive beliefs In mathematics, it consisted primarily of (30) paragraphs distributed on (4) three dimensions with alternatives (I agree / neutral / exhibitions) and its apparent validity has been verified by presenting it to a group of experts and composed of professors specialized in psychological and educational sciencesIt also verified its honesty and consistency, as its value reached (0,75), and the researcher prepared a test for productive thinking consisting of (24) objective paragraphs of multiple choice. Arithmetic, Pearson correlation coefficient, and T-test for one and two independent samples, the researcher reached the following results:- The students of the College of Basic Education possess a high level of productive thinking.- That college students enjoy a good level of cognitive beliefs in mathematics.- The presence of a positive and statistically significant correlation between productive thinking and cognitive beliefs among students of the College of Basic Education. In light of the results, the researcher reached a set of conclusions from the recommendations and proposals for the purpose of carrying out subsequent studies and studies